2015
DOI: 10.1016/j.egypro.2015.02.047
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Combustion and Emission Characteristics for Internal Combustion Rankine Cycle Engine under Different Water Injection Laws

Abstract: This paper discusses a novel oxyfuel combustion method named internal combustion rankine cycle (ICRC) used in reciprocating engines. Water is heated up through heat exchanger by exhaust gas and engine coolant, and then injected into the cylinder during the combustion to control the oxyfuel combustion temperature and reaction rate. Moreover, evaporation of the water mist increases the mass of working fluid so indicated thermal efficiency of the cycle is enhanced. This study investigates combustion and emission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 7 publications
1
15
0
Order By: Relevance
“…In ICRC engine concept, high-temperature and high-pressure water needs to be injected into the combustion chamber at firing top dead center (TDC), at this crank angle, the ambient pressure within the combustion chamber is significantly higher compared to traditional water injection conditions (during intake stroke or early compression stroke) in a conventional TDGI engine. The literature [50] shows that the maximum in-cylinder pressure of SI-ICRC and CI-ICRC is normally 7 MPa. In this section, the ambient pressure in the long tube is adjusted by continuous injection and modulation of the back-pressure valve.…”
Section: Water Injection Characteristics Under Different Ambient Presmentioning
confidence: 99%
“…In ICRC engine concept, high-temperature and high-pressure water needs to be injected into the combustion chamber at firing top dead center (TDC), at this crank angle, the ambient pressure within the combustion chamber is significantly higher compared to traditional water injection conditions (during intake stroke or early compression stroke) in a conventional TDGI engine. The literature [50] shows that the maximum in-cylinder pressure of SI-ICRC and CI-ICRC is normally 7 MPa. In this section, the ambient pressure in the long tube is adjusted by continuous injection and modulation of the back-pressure valve.…”
Section: Water Injection Characteristics Under Different Ambient Presmentioning
confidence: 99%
“…optimized engine load) lead to faster in-cylinder water evaporation, which provide larger increment in cycle efficiency optimization [21]. Although the DWI show huge potential in reducing abnormal combustion, the elimination of abnormal combustion is still a huge problem, therefore, within SI ICRC engine, large portion of exhaust gas recirculation (EGR) is needed for lowering in-cylinder temperature [22], the utilization of EGR limited the potential of ICRC concept as it shows negative impact on cycle efficiency optimization. In order to solve this problem, the compression ignition (CI) combustion mode is tested within the second generation of ICRC prototype engine, by utilization of homogeneous and heterogeneous charge compression ignition, a significant reduction of EGR utilization is realized, intake OF under homogeneous charge compression ignition (HCCI) varies from 70% to 100% [23], while OF decreased to 65% to 75% under traditional diffusion flame CI [24].…”
Section: Introductionmentioning
confidence: 99%
“…This concept of preheating the injected water by recovering some of the waste heat in oxy-fuel internal combustion engines is known as internal combustion Rankine cycle (ICRC). Better emissions of the ICRC engines have been also reported beside their improved efficiency [19]. It has been shown that the economic feasibility of the ICRC concept for automobiles could be superior to those based on fuel cells and biofuels [14].…”
Section: Introductionmentioning
confidence: 99%